PENGGUNAAN STRATEGI INKUIRI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK SD (Sindoro: Cendikia Pendidikan, 2025)
This study aims to examine the extent to which inquiry-based learning strategies can enhance critical thinking skills among elementary school students. The research was carried out using a classroom action research (CAR) approach over two learning cycles. The participants were third-grade students (Class III B) at SDN 03 Bandar Buat, Padang City. Data collection techniques included observing student learning activities, conducting interviews with the classroom teacher as a key informant, and administering written tests to assess students' critical thinking skills. The results of the analysis revealed a significant improvement in students’ critical thinking abilities following the implementation of inquiry-based learning. These findings demonstrate that the inquiry model holds strong potential in strengthening critical thinking development in elementary-level students.